A sigilografia portuguesa em tempos de Afonso Henriques - Maria do Rosário Barbosa Morujão (Medievalista)
This article aims at studying the beginnings of the Portuguese sigillography, which coincide with the government of Afonso Henriques. It synthesizes the knowledge that the current state of research allows about the early use of the seal in Portugal as a form of validating documents from episcopal, monastic and royal chanceries. A special importance is given to the royal seals, exploring a possible explanation for the eminently heraldic character that always marked the royal Portuguese sigillography, pointing to the importance as a warrior of Afonso Henriques, symbolized by his shield of arms, as a factor that gave legitimacy to his kingship and the independence of Portugal. His heraldry became itself the symbol of the new king and of the dynasty he gave birth to, thus remaining in all the Portuguese monarchs seals.